Evaluation of bowel by computed tomography enterography: comparing the water, mannitol and iodinated oral contrast - Naik, Pratik Narad; Kardam, Narendra Kumar; Gehlot, Kushal Babu; Ola, Sandeep Kumar; Nayak, Rakesh (International Journal of Research in Medical Sciences, 2024)
Background: Despite the small intestine’s size and significance, disorders of it are comparatively uncommon and can pose difficulties for diagnosis and treatment. Even with the advent of cutting-edge imaging methods like double balloon endoscopy and capsule endoscopy, diagnostic tests are still unable to accurately evaluate the bowel. Recent innovations, including capsule endoscopy and MRI have emerged as an alternative small bowel imaging techniques that can be performed without ionizing radiations. In this study we have compared Water, mannitol and iodinated oral contrast for assessing intraluminal distension, mucosal fold visualization and mural enhancement. Methods: A total of 150 patients fulfilling the selection criteria were studied. All patients of age group 25 to 70 years were included in the study. Patients with ileostomy, nasogastric tube in-situ and nil by mouth., with suspected intestinal obstruction, patient presenting with acute abdomen and fever were excluded. Results: It was observed that mannitol, homogeneity and mannitol group showed better bowel distension than iodinated contrast and plain water group (p<0.001), iodinated contrast and plain water group. (p<0.001). Mannitol group showed better wall visibility than iodinated contrast and plain water group. (p<0.001). Mannitol is better endo-luminal contrast agent than, iodinated contrast in water and plain water to assess the overall image quality. Conclusions: Computed tomography (CT) enterography using mannitol is excellent technique in better visualization of small bowel loops and thus helped to provide better diagnosis for intestinal abnormalities.